Biofabrication of advanced in vitro 3D models to study ischaemic and doxorubicin-induced myocardial damage. (24th January 2022) - Sharma, Poonam; Liu Chung Ming, Clara; Wang, Xiaowei; Bienvenu, Laura A; Beck, Dominik; Figtree, Gemma; Boyle, Andrew; Gentile, Carmine
Abstract: Current preclinical in vitro and in vivo models of cardiac injury typical of myocardial infarction (MI, or heart attack) and drug induced cardiotoxicity mimic only a few aspects of these complex scenarios. This leads to a poor translation of findings from the bench to the bedside. In this study, we biofabricated for the first time advanced in vitro models of MI and doxorubicin (DOX) induced injury by exposing cardiac spheroids (CSs) to pathophysiological changes in oxygen (O2 ) levels or DOX treatment. Then, contractile function and cell death was analyzed in CSs in control verses I/R and DOX CSs. For a deeper dig into cell death analysis, 3D rendering analyses and mRNA level changes of cardiac damage-related genes were compared in control verses I/R and DOX CSs. Overall, in vitro CSs recapitulated major features typical of the in vivo MI and drug induced cardiac damages, such as adapting intracellular alterations to O2 concentration changes and incubation with cardiotoxic drug, mimicking the contraction frequency and fractional shortening and changes in mRNA expression levels for genes regulating sarcomere structure, calcium transport, cell cycle, cardiac remodelling and signal transduction. Taken together, our study supports the use of I/R and DOX CSs as advanced in vitro models to study MI and DOX-induced cardiac damge by recapitulating their complex in vivo scenario.